Remote Sensing and GIS Accuracy Assessment - Lunetta, Ross (CRC Press, 2009)
The development of robust accuracy assessment methods for the validation of spatial data represents a difficult challenge for the geospatial science community. Obstacles to robust assessments include continuous data characteristics and positional errors, demanding ongoing development by GIS and remote sensing experts.